2019
DOI: 10.1111/jonm.12839
|View full text |Cite
|
Sign up to set email alerts
|

Presenteeism: Nurse perceptions and consequences

Abstract: Aims To describe factors leading to and consequences of nurse presenteeism. Background Presenteeism is more prevalent among nurses than other occupational groups. Existing literatures focuses on prevalence and consequences of presenteeism for patients, health care organizations, and nurses. However, we lack understanding of nurse perceptions of factors leading to and consequences of presenteeism. Methods A total of 295 free responses to a cross‐sectional survey were analysed using conventional content analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
67
2
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 68 publications
(76 citation statements)
references
References 29 publications
5
67
2
2
Order By: Relevance
“…Moreover, the profile of the studied sample did not change over time. In line with other nurse studies, we also observed a predominantly female population, referring to long work hours, high overload and complaints related to psychosocial stress [ 24 , 49 , 50 , 51 ]. Even so, our findings should be interpreted with caution, considering different work settings, professions and in particularly the current situations in hospitals.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…Moreover, the profile of the studied sample did not change over time. In line with other nurse studies, we also observed a predominantly female population, referring to long work hours, high overload and complaints related to psychosocial stress [ 24 , 49 , 50 , 51 ]. Even so, our findings should be interpreted with caution, considering different work settings, professions and in particularly the current situations in hospitals.…”
Section: Discussionsupporting
confidence: 91%
“…Rainbow [ 24 ], using a qualitative approach, described factors leading to nurse presenteeism. The author noted that nurses often prioritize hospital needs over their own health.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations